دراسة الشروط اللازمة لتحويل النفايات الناتجة عن مناشر الغرانيت إلى الحالة الزجاجية (Latakia University Journal -Basic Sciences Series, 2017)
تهدف الدراسة الى إمكانية استخدام نفاية الغرانيت الناتجة عن نشر الغرانيت في سوريا، والتي تعد ذات تأثير سلبي على البيئة إذ تلوث الهواء والماء والتربة وبالتالي تؤثر على الانسان والحيوان والنبات. لقد حدد التركيب الكيميائي لنفاية الغرانيت وتبين أنه مشابه للتركيب الكيميائي للزجاج لذا قمنا في هذا العمل بتحويل النفاية الناتجة عن مناشر الغرانيت الى الطور الزجاجي.تم تحضير الأطوار الزجاجية بطريقتين الأولى بإضافة رمل وكربونات الصوديوم والثانية بإضافة بوراكس وكربونات الصوديوم وتمت المعالجة الحرارية عند درجة حرارة (900-1000) درجة مئوية .تم التأكد من الحصول على الطور الزجاجي من خلال قياس XRDللعينات الناتجة وتم تحديد التركيب الكيميائي للزجاج الناتج بطريقة الصهارة القلوية ثم إجراء التحاليل الكيميائية اللازمة لتحديد نسبة الأكاسيد للعناصر، وفي المرحلة الثانية من العمل تم إجراء اختبارات على الزجاج الناتج (كثافته ومقاومته للحموض والأسس).لوحظ نقصان الكثافة بزيادة نسبة السيليكا وأكسيد الصوديوم وأكسيد البور، و لوحظ زيادة المقاومة للحموض والأسس بزيادة نسبة السيليكا وأكسيد الصوديوم، بينما عند إضافة البور نتج زجاج قليل المقاومة للحموض والأسس.This study ains for the ability of using granite waste emerged by sawing granite in Syria, which is considered as a negative effect on the environment , which pollutes the air , people, animal and planit. The chemical composition of granite waste was defined and it was clear that it is same as the chemical composition of glass . so we did this work by transforming the waste caused by granite sawmills to the glassy state.The preparation for the glassy states were done py two methods , the first by adding sand and sodium carbonate and second by adding borax and sodum cab ronate and the heattreatment was done at (900-1000 c) . The assurance of getting the glassy state through the XRD measure to the resulted samples was done . and the chemical composition of glass resulted by alkaline melting way was identified , then doing the chemical analyses needed to signify the percentage of oxides of the elements and in the second step of the worke , they have made tests on the resulted glass (its intensity, its resistance of acids and bases ).The decrease of intensity was noticed by the increase of silica concentration , sodium oxide and borates oxide , and it was noticed the increase of the resistance to the acids and alkalis by the increase of silica concentration and sodium oxide , but through adding the borates, the result was a glass less resistant to the acids and bases .